Denaturation behavior and conformational states of champedak galactose-binding lectin under various denaturing conditions / Nurul Iman Ahamed Kameel - Nurul Iman , Ahamed Kameel (2018)
Protein denaturation studies of champedak galactose-binding (CGB) lectin were carried out in order to understand its folding mechanism as it occurs in situ. Urea denaturation (0−9.0 M urea) of CGB lectin was studied using different spectral probes such as far-UV CD spectral signal, fluorescence intensity, emission maximum and ANS fluorescence intensity. CGB lectin showed a two-step, three-state transition in the presence of urea. The first transition (marked by the increase in the spectral signals) started at ~2.0 M urea and ended at ~4.5 M urea, while the second transition (characterized by the decrease in the spectral signals except emission maximum) showed the start- and the end-points at ~5.75 M and ~7.5 M urea, respectively, when analyzed by the emission maximum probe. Transformation of tetramer into monomer represented the first transition, whereas the second transition reflected the unfolding of monomer. Conformational analysis of the native, 5.0 M urea-denatured and 9.0 M urea-denatured states of CGB lectin was made using far-UV CD, Trp fluorescence and ANS fluorescence spectra. The hemagglutinating activity of the lectin gradually decreased with increasing urea concentrations and was completely lost at ~4.0 M urea. Acid denaturation (pH 7.0−1.0) of CGB lectin was studied using intrinsic fluorescence and ANS fluorescence measurements. The lectin remained stable up to pH 5.0 and showed local disordering in the vicinity of the protein fluorophores within the pH range, 5.0−3.5. Decrease in the pH from pH 3.5 to pH 2.5 led to structural transition, which can be ascribed to the dissociation of the tetrameric lectin into monomeric form. Further decrease in the pH up to pH 1.5 produced another transition, which specified the unfolding of monomers. Characterization of the conformational states obtained at pH 7.0, pH 2.5 and pH 1.5 based on intrinsic and ANS fluorescence spectra, gel chromatographic behavior and thermal denaturation confirmed the existence of the folded monomeric form at pH 2.5 and the unfolded state at pH 1.5. However, the acid-denatured state of CGB lectin at pH 1.5 retained significant residual structure, as evident from the greater loss of both secondary and tertiary structures in the presence of 6.0 M guanidine hydrochloride at pH 1.5. Anion-induced refolding below pH 1.5 was also evident from the ANS fluorescence results. Thermal denaturation of the acid-denatured states of CGB lectin resulted in formation of non-native β-structures. The influence of different polyols (ethylene glycol, erythritol, xylitol and sorbitol) on the acid-denatured states of CGB lectin at pH 2.5 and pH 1.5 was studied using ANS fluorescence, Trp fluorescence and far-UV CD measurements. The acid-denatured states of CGB lectin were stabilized against thermal denaturation in the presence of erythritol, xylitol and sorbitol as reflected by the shift of the thermal transition curves towards higher temperatures. On the other hand, ethylene glycol destabilized these states by shifting the thermal transition curves towards lower temperatures. Presence of erythritol, xylitol and sorbitol in the incubation mixture was found to stabilize the CGB lectin at both pH 2.5 and pH 1.5, as evident from the burial of the hydrophobic clusters and decreased polarity around Trp residues. Based on the spectral data, both sorbitol and erythritol appeared to exude relatively better stabilizing effect towards the secondary and tertiary structures of the acid-denatured states of CGB lectin. On the other hand, ethylene glycol was shown to destabilize it.